Presynaptic action of agkistrodotoxin on neuromuscular transmission - Yang Qin-zhao; Xu Ke (Acta Pharmacologica Sinica, 2016)
On rat phrenic nerve-diaphragm preparations agkistrodotoxin (ATX) selectively blocked the ACh release from the nerve endings without effect on the compound action potential of the nerve trunk, the terminal action potential, the contractile response of muscle to direct stimulation and the membrane potential of the muscle fibres. When the transmission was blocked by ATX, the ACh sensitivity of the chick biventer cervicis muscles remained unchanged. The unsustained tetanus with post-tetanic potentiation was observed on the ATX-treated preparations. The frequency of the mepp was increased at first and then decreased by ATX. In the late stage of the ATX action the successive epp's at 100 Hz maintained the amplitude as the first one in the train. The characteristics of all these changes caused by ATX were similar to those by β-bungarotoxin.